Effects of cholinergic antagonists on ghrelin release and expression in the crop, proventriculus, and duodenum of newly hatched chickens - Scanes, Colin Guy; Jaszcza, Klaudia; Pierzchala-Koziec, Krystyna (Frontiers in Physiology, 2025)
The aim of this study was to evaluate the effect of the cholinergic receptor antagonists on ghrelin (GHRL) expression and release from parts of the gastrointestinal system in an unique animal model—newly hatched chickens. Ghrelin was released from explants of the crop, proventriculus, and duodenum tissues in vitro. The expression of GHRL, along with that of ghrelin O-acyltransferase (GOAT) and growth hormone secretagogue receptor (GHSR-1a), was also observed in the crop, proventriculus, and duodenum. This is the first report on ghrelin expression, synthesis, and release in the avian crop. The release and expression of ghrelin, together with ghrelin-related parameters (expression of GOAT and GHSR-1a), were influenced by incubation with cholinergic antagonists, particularly in gastrointestinal explants from chicks within 2 h of hatching. For instance, there was increased release of ghrelin from crop or proventriculus explants from newly hatched chicks in the presence of hexamethonium. In addition, the expressions of ghrelin, GOAT, and GHSR-1a were increased in the presence of hexamethonium in crop explants from newly hatched chicks. In contrast, the release of ghrelin from duodenal explants was decreased in the presence of either atropine or hexamethonium in both newly hatched and 1-day-old chicks. There were relationships between ghrelin release and expression and also with GOAT and GHSR-1a expression, particularly in crop explants from newly hatched chicks. For instance, there were strong relationships (adjusted R2 > 0.84) between the expression of ghrelin, GOAT, and GHSR in tissue incubated with cholinergic antagonists. This is a novel report demonstrating ghrelin release and synthesis from three regions of the avian gastrointestinal tract. It also demonstrates the cholinergic control of ghrelin release and synthesis.